2022
DOI: 10.21467/ajss.10.1.52-62
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 School Closures in Uganda and their Impact on the Well-being of Teachers in Private Institutions in Semi-urban Districts

Abstract: Objective: This article explored how teachers were supported for continued professional growth and on their general well-being before and after the onset of the COVID-19 pandemic. Experiences of teachers of private schools in Semi-Urban districts during COVID-19 Wave 1&2 lockdown in Uganda are explored. It assess professional growth aspects and their well-being before and during closure of education institutions. The study illustrates challenges experienced by the teachers as well as coping strategies adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In line with the bulk of the literature on the topic, the key results revealed that (i) the first-wave COVID-19 lockdown negatively impacted TWB consistently across all three phases of the study, as evidenced in secondary teachers' diminished physical health and well-being, while (ii) a statistically significant correlation with autonomous teacher work motivation, as reflected in individual's desire to work and level of satisfaction and pleasure achieved upon work completion, foregrounded the salient role of this variable in fostering TWB in times of crisis. These findings concur with the overall decreased TWB levels and intense psychological strain experienced by teachers in private secondary schools within the socio-economically deprived context of semi-urban districts in Uganda after the onset of the COVID-19 pandemic, as reported by [119] and reflected by negative teacher identity self-perceptions, a fear of a lack of financial support for subsistence, and an increase in incidents of domestic violence throughout the 2020 lockdown period. Similarly, 70% of all teachers in Blaine's [120] study reported having considered leaving the profession due to intermittent school closures and uncertainty surrounding the government's response and policies on COVID-19.…”
Section: B Studies In Primary and Secondary Educationsupporting
confidence: 80%
See 3 more Smart Citations
“…In line with the bulk of the literature on the topic, the key results revealed that (i) the first-wave COVID-19 lockdown negatively impacted TWB consistently across all three phases of the study, as evidenced in secondary teachers' diminished physical health and well-being, while (ii) a statistically significant correlation with autonomous teacher work motivation, as reflected in individual's desire to work and level of satisfaction and pleasure achieved upon work completion, foregrounded the salient role of this variable in fostering TWB in times of crisis. These findings concur with the overall decreased TWB levels and intense psychological strain experienced by teachers in private secondary schools within the socio-economically deprived context of semi-urban districts in Uganda after the onset of the COVID-19 pandemic, as reported by [119] and reflected by negative teacher identity self-perceptions, a fear of a lack of financial support for subsistence, and an increase in incidents of domestic violence throughout the 2020 lockdown period. Similarly, 70% of all teachers in Blaine's [120] study reported having considered leaving the profession due to intermittent school closures and uncertainty surrounding the government's response and policies on COVID-19.…”
Section: B Studies In Primary and Secondary Educationsupporting
confidence: 80%
“…Self-reported high TWB levels were reported in only four studies and were mainly associated with an increased sense of work engagement, work meaningfulness, job commitment [110,111], and persistence to overcome COVID-19 and job productivity in terms of enhanced online teaching self-efficacy skills [116,117]. No noteworthy TWB developmental changes were recorded throughout the prolonged period of the COVID-19 pandemic [118,119], while findings with respect to TWB variance by gender and age of the samples included in each study were far from conclusive: (i) reported physical and psychological TWB levels were not found to significantly vary overall [101][102][103], with the exception of two studies where female schoolteachers exhibited higher levels of psychological well-being, while (ii) senior teachers tended to exhibit greater resilience and willingness to overcome current teaching difficulties and survive using work engagement [104], stressing the importance of adequate support provided at the school management level to boost their professional TWB level [108].…”
Section: Research Question 1: Twb Status During the Covid-19 Eramentioning
confidence: 98%
See 2 more Smart Citations